The first one, 5 times z to the power of negative three, is equal to 1 divided by 5 times z to the power of a positive three.
The second is one over 5z to the power of positive three.
2007-01-14 06:57:09
·
answer #1
·
answered by ZZ 4
·
0⤊
1⤋
No they dont equal the same thing
5z‾³ = 5/z^^3
(5z)‾³ = 1 / ( 5z) ^^ 3 = 1 / 125z^^3
2007-01-14 14:24:22
·
answer #2
·
answered by SKSK2006 1
·
0⤊
0⤋
The answer is very tricky. In 5z‾³, it is basically telling you 5 times z‾³, which is (5)/(z³). With (5z)‾³, it is telling you that it is (5z) to the power of negative three. The answer is (1)/[(5z)³] or 1/(125z³). Hope that helps
2007-01-14 14:20:08
·
answer #3
·
answered by David 1
·
1⤊
0⤋
David is correct. To understand why negative powers work like this, consider that dividing a power term by its base reduces the exponent by one. So for example (assuming a non-zero z):
z^3 / z = z^(3-1) = z^2
z^2 / z = z^(2-1) = z^1 (=z)
z^1 / z = z^(1-1) = z^0 (=1)
z^0 / z = z^(0-1) = z^-1 (= 1/z)
z^-1 / z = z^(-1-1) = z^-2 (= 1/z^2)
Etc.
2007-01-14 14:31:48
·
answer #4
·
answered by Groucho Returns 5
·
0⤊
0⤋
5z^-3 = 5(1/z^3) = 5/z^3
(5z)^-3 = 1/(5z^3)
2007-01-14 14:18:40
·
answer #5
·
answered by Beth 1
·
1⤊
0⤋
Well, it has to do with order of operations
The first one is like this. Five times Z to the negative third power
The second one is like this. The product of Five times Z, all taken to the negative third power.
That seriously changes the equation.
2007-01-14 14:17:36
·
answer #6
·
answered by Josh 5
·
1⤊
0⤋
Remember the rules:
1) a^(-n)=1/(a^n)
Ex. 5^-2=1/(5^2)=1/25.
2) (ab)^n = a^n * b^n
Ex. (7a)^2 = 7^2 * a^2 = 49a^2.
And remember the order of operations.
2007-01-14 14:19:11
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
(5x)^3 =5^3*x^3 = 125x^3
5x^3 = 5x^3.
2007-01-14 14:19:48
·
answer #8
·
answered by Dr Dave P 7
·
0⤊
0⤋